Ballistic strength of multi-layer fabrics against fragment simulating projectiles - Ma, Ying (Kansas State University, 2017)
Ballistic performance of textile fabric is affected by numerous elements, such as fabric architecture, material property, and projectile characteristics. Near fiber-level microstructures of soft body armor composed of multi-layer Kevlar KM-2 fabrics are generated for numerical simulation. The modified digital element approach (DEA) is applied to determine the ballistic limit of textile fabrics against fragment simulating projectiles (FSP). Different from other numerical models, the DEA takes a considerable amount of fiber-level detail into consideration and models the fabric at filament-level. In this approach, fabric is an assembly of yarns weaved and relaxed into pre-arranged pattern; yarn is simulated as a bundle of digital fibers. When the number of digital fibers per yarn reaches the number of actual fibers per yarn, fiber-level simulation is achieved. The DEA model successfully simulates real scale multi-layer fabric impacted by spherical projectile and accurately predicted fabric displacement and failure mechanism. It was assumed that the digital fiber is fully flexible and its bending rigidity is negligible. Shear force was thus neglected. However, for projectiles with sharp edge(s), such as FSP, due to resultant shear force, fabric failure starts where it interacts with projectile edge. As a result, the numerical results derived from the previous DEA overestimated the impact strength of fabrics against projectiles with shape edges. Therefore, shear force and fiber bending rigidity must be considered. In the modified DEA approach, numerical tests are employed to determine the effective bending rigidity of digital fiber. A combined tension-shear failure model is then incorporated into the DEA in order to calculate the shear force applied to fibers. The 3-D microscope is applied to measure the radius of FSP along the edge. The surface of the FSP is meshed into triangle elements. A unique algorithm is developed and employed to search contacts between textile fabric and projectile of arbitrary shape. In this research, first, an overview of ballistic impact analysis is discussed; the previous DEA model used in simulating ballistic impact and penetration process is presented. Second, the modified DEA approach used in simulating arbitrary shape projectile perforation process is established and verified. The method of searching and calculating contacts between textile fabric and solid body projectile is explained. The convergence and accuracy of digital element mesh are investigated statistically using tension-shear failure model. Third, fabric shear force and fiber bending rigidity are investigated using tension-shear failure model. The effective digital fiber area moment of inertia is numerically determined. Fourth, standard ballistic tests of real scale multi-layer Kevlar KM2 fabrics are simulated using FSP. Numerical results are compared to high-resolution experimental test data. The modified DEA is validated.
Keywords: Ballistic simulation; Textile mechanics; Digital element analysis; Impact resistant